Semantic Flows of Tree Symbolism: (H. Matevosyan - M. Galshoyan - V. Petrosyan) - Arzumanyan, Armenuhi (Bulletin of Yerevan University B: Philology, 2024)
The image of a tree, the tree of life as a symbol of the path to existence, has been preserved in the traditions of various peoples, becoming one of the original manifestations of folklore thinking. Different peoples had different symbolic layers of the tree of life, but the main symbolism was subconsciously the same. It symbolizes the gradual development of life, which is explained by the sense of the rooting, branching and fruiting of the tree.Later on, the semantic flows of tree symbolism penetrated into the field of creative thinking, becoming an interesting unit for creating images. The semantic flows of creating the symbolism of the image of a tree in fiction are mainly three-layered: the tree as the spiritual beginning of identity, the tree as a process of survival with its divergent directions, the tree as the end of the path of life striving for the starting point, taking into account gravity. "The Beginning" by G. Matevosyan, "The Lonely Tree" by M. Galshoyan and "The Lonely Walnut Tree" by V. Petrosyan are distinguished by interesting artistic solutions of these semantic flows of the image of a tree, in which the created figurative structures, equipped with original decompositions of the semantic flows of the symbolism of the image of a tree, generalize the biophilosophy of the path the existence of a species, a nation.
Keywords: symbol; semantic flows; biophilosophy; ideological issues; means of creating images